Pre-treatment preferences and characteristics among patients seeking in vitro fertilisation. - Walsh, A; Collins, G; Le Du, M; Walsh, D; Sills, E (2009)
BACKGROUND: This study sought to describe patient features before beginning fertility treatment, and to ascertain their perceptions relative to risk of twin pregnancy outcomes associated with such therapy. METHODS: Data on readiness for twin pregnancy outcome from in vitro fertilisation (IVF) was gathered from men and women before initiating fertility treatment by anonymous questionnaire. RESULTS: A total of 206 women and 204 men were sampled. Mean (+/- SD) age for women and men being 35.5 +/- 5 and 37.3 +/- 7 yrs, respectively. At least one IVF cycle had been attempted by 27.2% of patients and 33.9% of this subgroup had initiated >/=3 cycles, reflecting an increase in previous failed cycles over five years. Good agreement was noted between husbands and wives with respect to readiness for twins from IVF (77% agreement; Cohen's K = 0.61; 95% CI 0.53 to 0.70). CONCLUSION: Most patients contemplating IVF already have ideas about particular outcomes even before treatment begins, and suggests that husbands and wives are in general agreement on their readiness for twin pregnancy from IVF. However, fertility patients now may represent a more refractory population and therefore carry a more guarded prognosis. Patient preferences identified before IVF remain important, but further studies comparing pre- and post-treatment perceptions are needed.